Female DJs and electronic music producers in South Africa: thoughts on (under)representation, gendered technologies and collective agency - Joannou, Michelle Helen (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2024.